PLANEJAMENTO DAS ROTAS DE NAVIOS ALIVIADORES PARA RETIRADA DE ÓLEO PRODUZIDO DE PLATAFORMAS OFFSHORE DE PETRÓLEO CONSIDERANDO MÚLTIPLOS COMPARTIMENTOS, MÚLTIPLOS PORTOS E MÚLTIPLAS VIAGENS - Dias, Jeani dos Santos da Silva (2021)
Oil is often produced in locations far from where it will be refined and distributed. In Brazil, most of the oil production occurs in the sea where the oil is stored on platforms until the moment of its transfer to the ports. As the capacity of the oil storage tanks on each platform is limited, it is necessary to adopt some methodology to remove the volume produced to maintain continuous production. The collection of oil produced by ships is one of these methodologies and involves several operational restrictions. Among the restrictions we can mention the type of ship that can dock at each platform and port, the transport capacities of each ship, the need to keep different types of oil separate on the ship, and the initial and final moment to start the withdrawal of oil in each request to remove oil from the platform so that it does not have to stop production if this capacity is fully occupied. The decision of which ships will collect the different types of oils produced by each platform, in which sequence and in which ports the ships will deliver oil, from a series of available ports, make routing difficult. To carry out this planning, a new mathematical model is proposed considering several trips, multiple ports, multiple holds, and the restrictions mentioned to reduce the cost of transportation. 33 instances were created based on the largest Brazilian oil exploration and production company. CPLEX 12.10 was used to solve the model and the reduction in the total cost was up to 17.8% and the decrease in the total distance traveled by the ships was up to 13.3%. The proposed method proved to be applicable to travel planning to meet the service requests of the platforms, as well as a tool to support strategic decisions.